(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The problem of self-tuning databases has been veryimportant for the last 10 years. Commercial database systems have been addingfeatures for a long time and have now reached a level of complexity that makesthem a difficult choice as a central platform for information services ore-commerce. It is critical that database systems be easy to manage, predictablein their performance characteristics and, ultimately, self-tuning. Self-tuningdatabase technology is bound to build on mathematical models and to provideproper engineering into system components.Today’s DBMSs should be knob-free andmust be able to adapt as conditions change, without human intervention. Anautonomic DBMS should be capable of managing and maintaining itself as well.This paper examines the characteristics that a DBMS should have in order to beconsidered autonomic.Optimization of self-tuning models strives to minimize aprogrammable goal function that reflects the system designer’s preferences andthe system behavior.